Accruals, real earnings management, and CEO demographic attributes in emerging markets: Does concentration of family ownership count? - Safia Abdo Ali Al-Begali; Lian Kee Phua (Cogent Business & Management, 2023)
The present study utilizes agency theory and the upper echelons theory (UET) to investigate whether there is a moderating effect of family ownership concentration (FOWC) on the association between CEO demographic attributes and two forms of earnings management (EM), specifically accruals earnings management (AEM) and real earnings management (REM). Additionally, this study investigates whether CEO demographic attributes affect EM (AEM and REM) in Jordanian companies. The study sample includes 137 companies listed on the Amman Stock Exchange (ASE) from 2017 to 2021, with the banking and insurance sectors excluded, resulting in 685 company-year observations. To accomplish the study's goals, feasible generalized least squares estimation (FGLS) regressions were applied. The findings indicate that CEO non-duality and age decrease REM and improve the quality of financial reporting (QFR). However, they indicate that CEO age increases AEM, and family ownership concentration enhances the power of older CEOs to engage in AEM and affects QFR. The study finds that a CEO with high education does not affect EM but that the presence of family ownership increases a CEO's capacity with high education to reduce EM (AEM and REM) and generate trustworthy financial reports. However, we don't find any relationship between CEO gender and EM (AEM &REM), but family ownership increases male CEOs' power to engage in AEM. In addition, the outcome shows that family ownership concentration interacts with CEO non-duality and leads to restricting REM and engagement in AEM practices. This study is among the earliest attempts to examine how family ownership concentration affects the connection between CEO demographic attributes and EM, using both types of EM (AEM and REM). Thus, the results of this study are significant in providing meaningful insights for various stakeholders, such as management, investors, and owners, about the QFR and EM practices in emerging markets. Also, the outcomes of this study can contribute significantly to the existing literature on CEO characteristics, family ownership concentration, and EM practices. The findings can be used by the board of directors, policymakers, and regulators to re-evaluate the selection criteria for CEOs based on specific characteristics that can affect QFR. However, the results may not be applicable to markets that are characterized by dispersed ownership structures, where family ownership is not a dominant factor.
Keywords: 650; CEO demographic attributes; earnings management; family ownership concentration; Jordanian companies